The incidence of injury in male field hockey players: A systematic review and meta-analysis - Rees, H.; Persson, U. M.; Delahunt, E.; Boreham, C.; Blake, C. (Physical Therapy in Sport, 2021)
Objective Few studies have investigated injury incidence in field hockey. The aim of this systematic review was to determine the incidence and characteristics of injury in male field hockey athletes.